Predicted gamma-ray image of SN 1006 due to inverse Compton emission - Petruk, O. (2009)
We propose a method to synthesize the inverse Compton (IC) γ-ray image of a supernova remnant starting from the radio (or hard X-ray) map and using results of the spatially resolved X-ray spectral analysis. The method is successfully applied to SN 1006. We found that synthesized IC γ-ray images of SN 1006 show morphology in nice agreement with that reported by the High Energy Stereoscopic System (HESS) collaboration. The good correlation found between the observed very high energy γ-ray and X-ray/radio appearance can be considered as evidence of the fact that the γ-ray emission of SN 1006 observed by HESS is leptonic in origin, although a hadronic origin may not be excluded.